2013
DOI: 10.1093/cercor/bht131
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Characteristics of TMS-Induced Phosphenes Originating in Human V1 and V2

Abstract: One way to study the neural correlates of visual consciousness is to localize the cortical areas whose stimulation generates subjective visual sensations, called phosphenes. While there is support for the view that the stimulation of several different visual areas in the occipital lobe may produce phosphenes, it is not clear what the contribution of each area is. Here, we studied the roles of the primary visual cortex (V1) and the adjacent area V2 in eliciting phosphenes by using functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…In this study, we predicted a location of the maximum induced current to describe TMS-related effects relative to functional areas (Okamoto and Dan 2005). We found that stimulation of early visual areas produces phosphenes reliably (V1 40.8 %, V2d 45.4 %, V2v 41.7 % of stimulations) as previously reported (Abrahamyan et al 2011; Salminen-Vaparanta et al 2014). However, our results suggest that TMS induces a percept most frequently when aimed at dorsal visual areas (V3d 60 %, V3a 56.4 % of stimulations).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we predicted a location of the maximum induced current to describe TMS-related effects relative to functional areas (Okamoto and Dan 2005). We found that stimulation of early visual areas produces phosphenes reliably (V1 40.8 %, V2d 45.4 %, V2v 41.7 % of stimulations) as previously reported (Abrahamyan et al 2011; Salminen-Vaparanta et al 2014). However, our results suggest that TMS induces a percept most frequently when aimed at dorsal visual areas (V3d 60 %, V3a 56.4 % of stimulations).…”
Section: Discussionsupporting
confidence: 90%
“…However, in a previous study, participants reported slightly smaller phosphenes for stimulation of the dorsal visual cortex (V3d and V3a) compared to primary visual cortex V1 (Kammer et al 2005). In general, previous phosphene studies have reported that the overall appearance of phosphenes does not change significantly when different areas of the brain are stimulated (Kammer et al 2005; Salminen-Vaparanta et al 2014). This makes it unlikely that phosphene appearance systematically affected the stimulation outcome of this experiment.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…TMS inhibition possibly reflects the activity of GABAergic interneurons, but facilitation depends on the activation of intracortical fibers by the subthreshold stimulus, inducing the local release of glutamate (Oliveri and Caltagirone, 2006). TMS-induced electric field could induce phosphenes in the striate cortex (V1) of the macaque (Tehovnik and Slocum, 2007) and selective stimulated V1 and V2 (Salminen-Vaparanta et al, 2014) that were able to generate phosphene perception to a similar degree. It seems that TMS-induced phosphenes are due to the glutamate-related UPE.…”
Section: Glutamate Triggered Upe and Phosphenesmentioning
confidence: 99%